2016
DOI: 10.1007/s10198-016-0851-9
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of interventions targeting lifestyle change for the prevention of diabetes in a Swedish primary care and community based prevention program

Abstract: Background Policymakers need to know the cost-effectiveness of interventions to prevent type 2 diabetes (T2D). The objective of this study was to estimate the cost-effectiveness of a T2D prevention initiative targeting weight reduction, increased physical activity and healthier diet in persons in pre-diabetic states by comparing a hypothetical intervention versus no intervention in a Swedish setting.MethodsA Markov model was used to study the cost-effectiveness of a T2D prevention program based on lifestyle ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 44 publications
(82 reference statements)
0
26
0
Order By: Relevance
“…An overview of each model is outlined in Table 1, sorted by year of publication. Models were set in the USA (n = 6, 21%), 29,30,32,42,44,50 the UK (n = 3, 10%), 35,51,52 Australia (n = 3, 10%), 34,37,46 other European countries (n = 7, 24%), 33,36,39,41,43,47,54 the Americas (n = 3, 10%), 27,38,45 Asia (n = 5, 17%) 40,48,49,53,55 and in multiple countries (n = 2, 7%). 28,31 The type of intervention evaluated included screening programmes (n = 3, 10%), interventions (lifestyle and/or pharmacological) (n = 8, 28%), screening plus intervention (n = 17, 59%) and current care only (n = 1, 3%) (more detail in Appendix S2; Supporting Information Table SA.2.1).…”
Section: Resultsmentioning
confidence: 99%
“…An overview of each model is outlined in Table 1, sorted by year of publication. Models were set in the USA (n = 6, 21%), 29,30,32,42,44,50 the UK (n = 3, 10%), 35,51,52 Australia (n = 3, 10%), 34,37,46 other European countries (n = 7, 24%), 33,36,39,41,43,47,54 the Americas (n = 3, 10%), 27,38,45 Asia (n = 5, 17%) 40,48,49,53,55 and in multiple countries (n = 2, 7%). 28,31 The type of intervention evaluated included screening programmes (n = 3, 10%), interventions (lifestyle and/or pharmacological) (n = 8, 28%), screening plus intervention (n = 17, 59%) and current care only (n = 1, 3%) (more detail in Appendix S2; Supporting Information Table SA.2.1).…”
Section: Resultsmentioning
confidence: 99%
“…Among prevention, about 20% of the topics were allocated to primary prevention while the remaining 80% focused on secondary prevention such as screening tests. Teaching on topics about primary prevention, however, could be more beneficial for future doctors as primary prevention measures bear a larger and cost-effective impact within public health [36][37][38][39]. Surprisingly, pregnancy-related themes such as prenatal diagnostics were used as risk communication topics as often as cancer although they are ethically debatable, usually not paid by insurance companies, relevant only for pregnant women/their relatives and detect only 2% of genetically transmitted diseases; whereas cancerrelated health problems carry a much heavier burden [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…43 [38] used a €35,000/QALY threshold, while D'Andrea et al [39] and Areia et al [40] set a threshold of €37,000/QALY in Italy and Portugal, respectively. However, Neuman et al [41] and Naber et al [42] considered a higher cost-utility threshold (€50,000/QALY). According to the cost-utility thresholds used in these studies, providing a germline BRCA1/2 testing to HGEOC patients without family history of OC or BC and their gBRCA1/2m-positive relatives is cost-effective in Spain.…”
Section: Discussionmentioning
confidence: 99%
“…Our results of the one-way sensitivity analyses were not substantially different from the base case, and most of them were below the €37,000/QALY threshold. Besides, our PSA showed that 52.52% of our simulations fell below the €35,000/QALY threshold, 60.56% were below the €37,000/QALY threshold, and 89.12% were below the €50,000/QALY threshold [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%